Catalytic dehalogenation of halogenated pyridine donors under DOW-Phenol conditions - Bujis, Wim; Comba, Peter (European journal of inorganic chemistry, 2001)
Various halogenated pyridines (2-fluoropyridine, 2-chloropyridine, 2-bromopyridine, 3-bromopyridine, 2,5-dibromopyridine, and 3,5-dibromopyridine) are subject to catalytic reduction and substitution under DOW-phenol conditions; copper(I) benzoate is shown to play a key role in these processes. In the absence of copper(I), the halogenated pyridines do not react with benzoic acid, while after precipitation of copper(I) halide the dehalogenation process stops. Marked differences are observed between the copper(I)-catalyzed dehalogenation of the halopyridines and the previously reported dehalogenation of halogenated aromatics. While the copper(I)-catalyzed substitution of haloaryl compounds by benzoate makes only a minor contribution to the overall dehalogenation process, substitution of halopyridine compounds is at least as important as the reduction reaction. Furthermore, the reaction with halopyridine compounds is regioselective, in contrast to that with halogenated aryl compounds.